Experimental and theoretical research on the mechanical performance of totally recycled concrete under triaxial compression after high temperatures. (20th November 2020) - Meng, Ercong; Yu, Yalin; Zhang, Xianggang; Su, Yisheng
Highlights: TRC specimens were tested under triaxial compression after high temperatures. Failure forms of TRC are longitudinal, lamellar splitting and inclined plane shear. Initial deformation modulus of TRC is less affected by temperature when T  < 400 °C. Constitutive relation formulas for TRC after high temperatures were proposed. Abstract: The technology of using recycled aggregates in concrete to totally substitute natural aggregates to produce totally recycled concrete (TRC) has obvious environmental and economical importance. In practical engineering, concrete structures are always subjected to triaxial compression state and may be exposed to high-temperature working conditions. Thus, studying the mechanical performance of TRC under triaxial compression after high temperatures is crucial. In this work, 30 groups of Ф100 mm × 200 mm cylindrical TRC specimens were designed and tested under triaxial compression conditions after exposure to different high temperatures first. The failure modes of specimens were observed, and the stress–strain curves, bearing capacities, and initial deformation modulus were obtained. Then, the measured mechanical performance indices were analyzed, and the calculation formula of the triaxial bearing capacities for TRC specimens after high temperatures was proposed. Finally, the constitutive relations and failure criterion were examined on the basis of different national standards and Mohr–Coulomb theory, which can provide references for related theoretical studies and engineering applications of TRC.